2001
DOI: 10.1046/j.1365-8711.2001.04522.x
|View full text |Cite
|
Sign up to set email alerts
|

Black hole masses from power density spectra: determinations and consequences

Abstract: We analyse the scaling of the X‐ray power density spectra with the mass of the black hole in the examples of Cyg X‐1 and the Seyfert 1 galaxy NGC 5548. We show that the high‐frequency tail of the power density spectrum can be successfully used for the determination of the black hole mass. We determine the masses of the black holes in six broad‐line Seyfert 1 galaxies, five narrow‐line Seyfert 1 galaxies and two quasi‐stellar objects (QSOs) using the available power density spectra. The proposed scaling is clea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
81
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(90 citation statements)
references
References 87 publications
9
81
0
Order By: Relevance
“…A similar anti-correlation between the rate at which variability power is injected into the light curve and black hole mass has also been found for AGN optical variations (KBS09). Czerny et al (2001) find an anti-correlation between M BH and the frequency at which the PSD reaches a reference value, which is consistent with an anti-correlation between M BH and the amplitude of the high-frequency PSD. However, our result differs from most previous work in that we do not compute the variance over some range of timescales, directly from the observed light curve, but rather we fit a parameter ς , which is the rate at which variability power is injected into the light curve.…”
Section: Comparison With Black Hole Masssupporting
confidence: 85%
“…A similar anti-correlation between the rate at which variability power is injected into the light curve and black hole mass has also been found for AGN optical variations (KBS09). Czerny et al (2001) find an anti-correlation between M BH and the frequency at which the PSD reaches a reference value, which is consistent with an anti-correlation between M BH and the amplitude of the high-frequency PSD. However, our result differs from most previous work in that we do not compute the variance over some range of timescales, directly from the observed light curve, but rather we fit a parameter ς , which is the rate at which variability power is injected into the light curve.…”
Section: Comparison With Black Hole Masssupporting
confidence: 85%
“…One may reconcile the absence of power in the high frequency regime to the scattering of the X-ray photons in the wind from the companion WolfRayet star, reducing the amplitude of the fast X-ray variability (Berger & van der Klis 1994). If we reconcile the absence of power above 0.1 Hz to the reprocessing of the X-ray emission in the circumstellar environment, then this feature does provide an interesting sidelight to the paradigm which states that the variability time-scale scales linearly with the mass of the compact object (Hayashida et al 1998;Czerny et al 2001), and introduce an additional factor, viz. reprocessing in the dense circumstellar material, where it exists, into the picture.…”
Section: Power Density Spectrummentioning
confidence: 99%
“…The distinct feature of the power density spectra of the source is the shifting of the spectra towards low frequency regime (vis-a-vis the "normal" frequency regime of other Galactic X-ray binaries), corresponding to very massive black hole systems (Hayashida et al 1998;Czerny et al 2001). Sunyaev & Revnivtsev (2000) have compiled the power density spectra (multiplied by frequency) of the most common Galactic X-ray binaries, both neutron stars and black hole candidates (in their low/hard states).…”
Section: Power Density Spectrummentioning
confidence: 99%
“…The difference in time-scales could be explained by the difference in the mass of the compact object in the center of these objects. The results from these first studies made it clear that the observed AGN X-ray variations are most probably determined by BH mass (M BH ) rather than luminosity (Hayashida et al 1998;Czerny et al 2001;Uttley et al 2002), and even suggested that X-ray variability might be used as a tool to estimate M BH in these objects. McHardy et al (2006) were the first to demonstrate clearly that AGN are scaled-up versions of BHB.…”
Section: Introductionmentioning
confidence: 99%